Effects of acute psychological stress on athletic performance in elite male swimmers - Rano, J.; Fridén, C.; Eek, F. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: While physical activity has been shown to affect psychological as well as physiological stress responses, less research has explored the effects of acute stress on athletic performance. The current study hence aimed to investigate the effect of an acute psychological stress (APS) provocation on performance and plasma lactate concentration during a following 200-m swim race among elite male swimmers. Furthermore, associations between physiological stress responses (salivary cortisol and testosterone), and outcome measures (speed and lactate) were explored. METHODS: Twenty-three elite male swimmers participated in an experimental counterbalanced within-group repeated measures design consisting of an APS provocation followed by a 200-m race and, on a separate day, a control race without prior stress exposure. Salivary cortisol and testosterone were collected prior to each race. Race time was recorded, and serum lactate was collected immediately following, and five min after completed race. RESULTS: Race speed was significantly slower (1.53 [95% CI: 0.08-2.79] seconds) following the APS provocation than under control conditions. Prerace cortisol levels were positively associated with lactate response when preceding stress exposure was present (rho =0.483 immediately, and rho=0.429 five minutes post race, P<0.05). Under control conditions however, both increased testosterone (rho =-657, P=0.001) and cortisol (rho =-0.491, P=0.020) levels were associated with faster race times. CONCLUSIONS: The results indicated a negative impact of APS exposure on athletic performance. Further, potential beneficial effects on performance from physiological stress responses (as reflected by salivary cortisol and testosterone) may be diminished during performance following an APS provocation, compared with a regular non-provoked performance situation.